Evaluation of the Central Sensitization Inventory Score in elderly adults with musculoskeletal examination. Issue 4 (4th July 2021) - Ide, Koichiro; Yasuda, Tatsuya; Hasegawa, Tomohiko; Yamato, Yu; Yoshida, Go; Banno, Tomohiro; Arima, Hideyuki; Oe, Shin; Mihara, Yuki; Ushirozako, Hiroki; Yamada, Tomohiro; Watanabe, Yuh; et al.
Abstract: Objectives: The present study aimed to conduct an epidemiological survey of Central Sensitization Inventory (CSI) scores in an older adult population and to investigate the association between the CSI scores, age, sex, pain intensity, site of pain, and health-related quality of life (QOL). Methods: Participants were 373 Japanese adults aged ≥ 50 years who underwent a health checkup in 2018. We collected demographic data and clinical characteristics along with the CSI scores, QOL questionnaire, site of pain (neck, lower back, upper limb, and lower limb) and pain severity. We performed an epidemiological survey of the CSI scores and investigated the gender difference in CSI scores and the relationship between the CSI scores, site of pain, and QOL. Results: The prevalence of low back pain was the highest (67.6%). The average CSI score was 14.2 points; 8% of volunteers had a high (> 30) CSI score. The CSI scores among women were significantly higher than those among men ( p = .016). The CSI scores had a significantly moderate correlation with the numerical rating scale and QOL scores (all p < .001). Volunteers with neck pain showed the highest CSI scores (average 22.4 points). Conclusions: The CSI total score showed sex differences and had a significant correlation with pain severity and QOL. Study design: Cross-sectional study.